PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN - Dr. Ismail Razak, M.Si. (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
The purpose of this study was to analize the impact of product quality indicators on the satisfaction of customers. Primary data was obtained from customers of aqua in Transmart Carrefour Kalimalang, Jakarta Timur through admission filling of questionnaire by using scale of Likert. In this study is used purposive sampling method. Data analysis technique used in this study is simple and multiple linear regression. The results of this study indicated that performance, reliability, conformance, and durability positively and significant influenced the satisfaction of customers. The conclution of this study is that conformance was dominant than the other product quality indicators in influencing the satisfaction of customers.